Comparison of hair‐trapping methods for the long‐tailed goral - Hee‐Bok Park; Hee Cheon Park; Phil E. Cowan; Sungwon Hong (Wildlife Society Bulletin)
ABSTRACT In South Korea, there is a need for more ecological information about endangered herbivores such as the long‐tailed goral (Naemorhedus caudatus). This species lives in steep, rocky valleys and is difficult to trap and study. Noninvasive hair capture techniques have frequently been applied to carnivores to enable DNA or isotope analysis. Therefore, we assessed the effectiveness of hair‐trapping using a population of goral in the Wangpi River basin in South Korea. To compare efficiency of the different shapes of hair traps, we used barbed traps at 4 (2008) and 9 sites (2009), and a hook‐style trap (2010) with barbed traps at each of 15 sites. In 2008, we collected 15 hairs at all 4 sites with barbs. In 2009, we obtained 48 hairs at 8 of the 9 sites using barbs; and in 2010, we collected 99 hairs (barbed: 50 hairs, hook traps: 49 hairs) at 10 of the 15 sites using both traps. In 2010, the 2 shapes of hair traps were equally efficient at providing samples. We concluded that the hair‐trapping method allows for noninvasive monitoring of the endangered goral, and could be used to monitor other species in South Korea. © 2018 The Wildlife Society.